Fundamentals of engineering thermodynamics / Michael J. Moran, Howard N. Shapiro - Moran, Michael J. (John Wiley & Sons, 1998)
Presents a comprehensive and rigorous treatment of the subject from the classical perspective to offer a problem-solving methodology that encourages systematic thinking. Noted for its treatment of the second law, this text clearly presents both theory and application. The presentation of chemical availability has been extended by a cutting- edge discussion of standard chemical availability. Design applications and problems have been updated to include economic considerations. Environmental topics have also been expanded and updated. The new version of Interactive Thermodynamics (IT) is a powerful windows-based software program that now includes equation-solver, printing, graphing, data retrival and simulation capabilities.